When an antipassive isn’t an antipassive anymore: the Actor Voice Construction in Kelabit - Hemmings, C (John Benjamins, 2021)
This paper presents the Actor Voice (av) construction in Kelabit, a Western Austronesian language spoken in Northern Sarawak, Malaysia. It compares Kelabit av with prototypical antipassives and related constructions in the more conservative Western Austronesian languages, using case studies of West Greenlandic and Tagalog. On the basis of morphosyntactic, semantic and discourse diagnostics, the paper demonstrates that Tagalog av constructions have the semantic and discourse characteristics of antipassives but are syntactically transitive. In contrast, Kelabit av, which is also syntactically transitive, has a mixture of semantic and discourse properties: some antipassive-like but many active-like. This has important implications for Western Austronesian and the theory of alignment shift, as well as the ways in which antipassives vary and change over time.